PERENCANAAN GOLONGAN PEMBERIAN AIR UNTUK OPTIMASI PENYALURAN AIR MENGGUNAKAN ALGORITMA GENETIK - Gani Soehadi; Bambang Pramudya; Setyo Pertiwi; Erizal . (Jurnal Keteknikan Pertanian, 2006)
ABSTRACT This paper presents the improvement of block system planning of irrigation water in cikarang area for optimization of the irrigation water distribution by using Genetic Algorithm. A genotype representation of spatial allocation was proposed: a fixed-length genotype composed of four genes that represent spatial allocation determined by greedy algorithm. The process of optimizing genotype includes evaluation, selection, crossover, and mutation,. Evaluation process determined the fitness of the genotype based on the distance of water sources, availability of irrigation water, labor, mechines and delay of harvesting opertion of last-season crop. Several types of selection, crossover and mutation were tested to obtain the best processing sequence for optimizing the genotype. This approach was comared to a real block system problem determined by Perum Jasa Tirta II and the adventages of the approach were identified. Keyword: representasi, Algoritma Genetik, Irigasi